2008
DOI: 10.1021/pr800540h
|View full text |Cite
|
Sign up to set email alerts
|

The PI(3,5)P2 and PI(4,5)P2 Interactomes

Abstract: A comprehensive analysis of the phosphoinositide interactome has been performed using analogues of PI(3,5)P2 and PI(4,5)P2 phosphatidyl phospholipids which were immobilized onto Affi-10 beads or incorporated into liposomes for use as affinity absorbents with cytosolic extracts from colonic carcinoma cell lines. Affinity/LC/MS/MS experiments allowed identification of 388 proteins/protein complexes that appeared to interact specifically with the phosphoinositide targets: a number of novel potential phosphoinosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 130 publications
1
127
0
Order By: Relevance
“…It has been reported that talin FERM domains bind to negatively charged vesicles in solution (12,13,24,31,32). To confirm these observations, we used isothermal titration calorimetry (ITC) to measure the enthalpy of F0-F3 binding to large unilamellar vesicles (LUVs) composed of 90% POPC and 10% PtdInsð4;5ÞP 2 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been reported that talin FERM domains bind to negatively charged vesicles in solution (12,13,24,31,32). To confirm these observations, we used isothermal titration calorimetry (ITC) to measure the enthalpy of F0-F3 binding to large unilamellar vesicles (LUVs) composed of 90% POPC and 10% PtdInsð4;5ÞP 2 .…”
Section: Resultsmentioning
confidence: 81%
“…Similarly, the cytoskeletal protein talin-1, whose binding to the β3 cytosolic tail (CT) stabilizes the active conformation of αIIbβ3 (6)(7)(8), is sequestered away from the β3 CT (9). Besides interacting with integrins, talin-1 interacts with negatively charged phospholipids (10)(11)(12) and phosphoinositides (13)(14)(15)(16). Stimuli generated at sites of vascular damage recruit talin-1 to the platelet plasma membrane, thereby promoting αIIbβ3 activation (17)(18)(19).…”
mentioning
confidence: 99%
“…HRMS and 1 H, 13 C, and 31 P NMR spectra of all new compounds reported in this paper are available on the Journal's website.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…[8] The synthetic derivatives of these molecules were used to form liposomes for characterisation purposes. [13,14] However, it is not always desirable to form liposomes or higher-order aggregates when studying such compounds. Furthermore, the long-acyl-chain derivatives are not particularly soluble in water owing to their hydrophobicity, which can cause problems when studying the interactions of such compounds with polar macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…None of these proteins overlapped with the ones identified in the previous study. In a more comprehensive study, Holmes and colleagues have characterized and compared the interactomes of PtdIns(3,5)P 2 and PtdIns(4,5)P 2 (Catimel et al 2008) as well as PtdIns(3,4,5)P 3 (Catimel et al 2008;Catimel et al 2009) determined from the cytosolic extracts of colon cancer cells expressing WT PI3 kinase. PIs immobilized either onto beads or incorporated into liposomes were used for protein capture from the cytosolic extracts.…”
Section: Lipid-protein Interactomesmentioning
confidence: 99%